Optimizing the Extraction of Bioactive Compounds from Porphyra linearis (Rhodophyta): Evaluating Alkaline and Enzymatic Hydrolysis for Nutraceutical Applications - Pereira, Débora Tomazi; García-García, Paz; Korbee-Peinado, Nathalie; Vega, Julia; Señoráns, Francisco J.; López-Figueroa, Félix (MDPI, 2024)
Porphyra sensu lato is one of the most economically significant and widely cultured and consumed algae in the world. Porphyra species present excellent nutraceutic properties due to their bioactive compounds (BACs). This research aimed to find the most efficient aqueous extraction method for BACs by examining alkaline and enzymatic hydrolysis. Alkaline hydrolysis with 2.5% sodium carbonate (SC) and at 80 °C proved optimal for extracting all BACs (phycobiliproteins, soluble proteins, polyphenols, and carbohydrates) except mycosporine-like amino acids (MAAs), which were best extracted with water only, and at 80 °C. Enzymatic hydrolysis, particularly with the ‘Miura’ enzymatic cocktail (cellulase, xylanase, glycoside hydrolase, and β-glucanase), showed superior results in extracting phycoerythrin (PE), phycocyanin (PC), soluble proteins, and carbohydrates, with increases of approximately 195%, 510%, 890%, and 65%, respectively, compared to the best alkaline hydrolysis extraction (2.5% SC and 80 °C). Phenolic content analysis showed no significant difference between the ‘Miura’ cocktail and 2.5% SC treatments. Antioxidant activity was higher in samples from alkaline hydrolysis, while extraction of MAAs showed no significant difference between water-only and ‘Miura’ treatments. The study concludes that enzymatic hydrolysis improves the efficiency of BACs extraction in P. linearis, highlighting its potential for the nutraceutical industry, and especially with respect to MAAs for topical and oral UV-photoprotectors.
Keywords: Algas; alkaline hydrolysis; biological active compounds; bioeconomics; biorefining; enzymes; extraction methods; Porphyra; nutraceuticals